BRAND POTENTIAL OF UNIVERSITY IN THE CONTEXT OF INTERNATIONALIZATION OF EDUCATION IN RUSSIA: ARCTIC VECTOR, OIL AND GAS DOMINANT - O. I. Belyaeva; G. V. Korshunov (Высшее образование в России)
The article highlights the aspects of University branding, presents the activities of Ukhta State Technical University aimed at internationalization of education and promotion of USTU brand in the near and far abroad. Special attention is paid to the Arctic vector of University development and oil and gas dominant as the components of the brand potential of USTU.